A clinical practice guideline for the management of the foot and ankle in rheumatoid arthritis - Ramos-Petersen, Laura; Reinoso-Cobo, Andrés; Ortega-Ávila, Ana Belén; Garcia-Campos, Jonatan; Bernal, Jose-Antonio; Cantero-Téllez, Raquel; Martín-Martín, Jose-María; Caliz-Caliz, Rafael; Tejero, Sergio; Cano-García, Laura; Gijón-Noguerón, Gabriel (Springer, 2024)
Rheumatoid arthritis causes progressive joint destruction in the long term, causing a deterioration of the foot and ankle. A clinical practice guideline has been created with the main objective of providing recommendations in the field of podiatry for the conservative management of rheumatoid arthritis. Thus, healthcare professionals involved in foot care of adults with rheumatoid arthritis will be able to follow practical recommendations. A clinical practice guideline was created includ- ing a group of experts (podiatrists, rheumatologists, nurses, an orthopaedic surgeon, a physiotherapist, an occupational therapist and patient with rheumatoid arthritis). Methodological experts using GRADE were tasked with systematically reviewing the available scientific evidence and developing the information which serves as a basis for the expert group to make recommendations. Key findings include the efficacy of chiropody in alleviating hyperkeratotic lesions and improv- ing short-term pain and functionality. Notably, custom and standardized foot orthoses demonstrated significant benefits in reducing foot pain, enhancing physical function, and improving life quality. Therapeutic footwear was identified as crucial for pain reduction and mobility improvement, emphasizing the necessity for custom-made options tailored to individual patient needs. Surgical interventions were recommended for cases which were non-responsive to conservative treatments, aimed at preserving foot functionality and reducing pain. Moreover, self-care strategies and education were underscored as essential components for promoting patient independence and health maintenance. A series of recommendations have been created which will help professionals and patients to manage podiatric pathologies derived from rheumatoid arthritis.
Keywords: Pies; Tobillos; Artritis reumatoide; Cuidados de enfermería; Foot; Ankle; Care management; Patient; Rheumatoid arthritis